Interfering with emotional processing resources upon associative threat memory reactivation does not affect memory retention - Chalkia, Anastasia (Sci Rep, 2019)
Ample evidence suggests that memories enter a labile state upon retrieval, requiring reconsolidation processes in order to be retained. During this period of instability, various interventions can be applied to modify problematic memories. A novel behavioral intervention was designed, aimed at disrupting amygdala-based cognitive processing following the retrieval of a conditioned threat memory, in order to prevent its reconsolidation. We fear-conditioned participants on day 1, and reactivated their memory on day 2. Following reactivation, the reactivation plus emotional working memory task (R + EWMT) group completed an EWMT, while the reactivation only (RO) group served as a no-task control. On day 3, all participants were tested for memory retention, followed by a test for sensitivity to reinstatement. We observed successful acquisition and reactivation in fear-potentiated startle responding, skin conductance responding and US expectancies in both groups. Differential fear responding was fully preserved in the R + EWMT group relative to the RO group at the beginning of retention testing, and both groups were comparably sensitive to reinstatement. Thus, we failed to obtain any evidence that the execution of an EWMT after threat memory reactivation impairs reconsolidation. Further research is indicated to clarify whether threat memory reconsolidation can be disrupted by taxing relevant WM resources.